KONSTRUKSI REALITAS PENAHANAN ANGELINA SONDAKH SEBAGAI TERSANGKA KASUS DUGAAN SUAP PEMBAHASAN ANGGARAN - Huda, Giskal Nurul (Universitas Prof. Dr. Moestopo (Beragama), 2013)
Angelina Sondakh retained by the Commission as a suspect in the alleged bribery related to the discussion of theparliamentary budget and Kemendikbud Kemenpora started singing of his predecessors , Muhammad Nazaruddinand Mindo Rosalina Manulang who first arrested by the KPK . Accordingly, the Commission conduct aninvestigation and assign Angelina as a suspect in the alleged bribery homestead project athletes since 3 February2012. However , in the event of his arrest , the Commission set the suspects in the alleged bribe to Angelina atthe two ministries , namely the case of projects related to house athletes Kemenpora and projects in a number ofcases related to Kemendikbud university . Almost all mass media in Indonesia, especially the print media doesnot escape the news by presenting each point of view on the newspaper page . To the authors chose two leadingnewspapers in Indonesia, namely , the newspaper Kompas and Tempo .The purpose of this study is to see how the newspaper Kompas and Tempo frame , construct , and respond toevents on the arrest of Angelina Sondakh as suspects in the alleged bribery in the budget discussion and KemendikbudKemenpora .Methodologically , this study uses a constructivist paradigm , the qualitative descriptive research , this study alsouses framing analysis model of Robert n entman as analytical tools to the theory of social construction of realitybelongs to peter L.berger and Thomas Luckmann. Results of this study showed a different frame between thenewspaper Kompas and tempo, in framing the incident .Kompas newspapers construct news about Angelina Sondakhretained by the Commission as a suspect in the alleged bribery of parliamentary budget debate , as politicaland legal issues . At the event Angelina Sondakh detention, Compass presents the political elements of the event. However , related legal issues , Compass issues such events lead towards disclosure cases. While newspapersTempo , see this case as a matter of law. Tempo did not tell the political elements of the event.Detention of newsevents , Tempo problem immediately ushered towards disclosure cases.